Analisis Kuat Tekan Dan Kuat Lentur Beton Yang Menggunakan Serat Abaca - Randan, Yurike; Setiawan, Arman; Yusuf, Andi Rumpang (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Currently, various very rapid developments occur in the world of construction. One example is the development of concrete technology. Concrete is the result of technological engineering, concrete is produced from a mixture of cement, fine aggregate (sand), coarse aggregate (gravel), and water. Concrete is also usually added with certain materials to support the quality of the concrete. In this study, abaca fiber was used as an additive in the concrete mixture. The purpose of this study was to obtain the effect of adding abaca fiber by 0.5%, 0.75%, 1%, 2.72%, 4.08% and 5.44% on the weight of cement. Samples of test specimens were made of 50 samples, 20 samples of normal concrete and 30 samples of variation concrete. Treatment of the test object is done by soaking the concrete for 28 days. The compressive strength and flexural strength of concrete were tested when the age of the specimen reached 28 days. The results of this test indicate that the 0.5% variation of concrete has a compressive strength of 29.23 Mpa and a flexural strength of 5.33 Mpa. This shows that the addition of abaca fiber produces higher compressive and flexural strength values than normal concrete.